Seed germination ecology of hood canarygrass (Phalaris paradoxa L.) and herbicide options for its control - Vicent Kibasa; Gulshan Mahajan; Bhagirath Singh Chauhan (Scientific Reports, 2022)
Abstract Hood canarygrass (Phalaris paradoxa L.) is a problematic weed in winter crops of Australia. Experiments were conducted to determine the effects of environmental factors on seed germination of P. paradoxa and wheat (Triticum aestivum L.) and herbicide options for P. paradoxa control. Results revealed that P. paradoxa had higher germination (> 89%) at a temperature range from 15/5 ℃ to 25/15 ℃ [day/night (12 h/12 h] compared with 30/20 ℃ and 35/25 ℃. At a temperature regime of 30/20 ℃, P. paradoxa had 1% germination; however, wheat at this temperature range resulted in 79% germination. Exposure of seeds of P. paradoxa to > 150 ℃ pretreatment (radiant heat for 5 min) resulted in no germination. These results suggest that infestation of P. paradoxa could be reduced by residue burning or by planting wheat crops early in the season when the temperature is relatively high. At a water potential of -0.8 MPa, seed germination of P. paradoxa and wheat was 75 and 96%, respectively. Similarly, at the highest salt concentration (200 mM sodium chloride), seed germination of P. paradoxa and wheat was 73 and 79%, respectively. These observations suggest that like wheat, P. paradoxa is also highly tolerant to water and salt stress conditions, therefore, it could invade the agro-ecosystem under water and salt stress situations. Germination of P. paradoxa was found to be low (10%) on the soil surface, suggesting that no-till systems could inhibit the germination of P. paradoxa. Pre-emergent (PRE) herbicides, namely cinmethylin, pyroxasulfone, and trifluralin, provided 100% control of P. paradoxa; however, in the presence of 2 t ha−1 of residue cover, pyroxasulfone provided better control of P. paradoxa compared with other herbicides. Post-emergent (POST) herbicides clethodim, haloxyfop, and paraquat provided excellent control of P. paradoxa, even if the plant size was large (10-leaf stage). Knowledge generated from this study will help in strengthening the integrated management of P. paradoxa.